UV radiation sensitivity of bacteriophage PhiX174 - A potential surrogate for SARS-CoV-2 in terms of radiation inactivation - Laura Weyersberg; Florian Sommerfeld; Petra Vatter; Martin Hessling (AIMS Microbiology, 2023)
To minimize health risks, surrogates are often employed to reduce experiments with pathogenic microorganisms and the associated health risk. Due to structural similarities between the enveloped RNA-viruses SARS-CoV-2 and Phi6, the latter has been established as a nonpathogenic coronavirus surrogate for many applications. However, large discrepancies in the UV log-reduction doses between SARS-CoV-2 and Phi6 necessitate the search for a better surrogate for UV inactivation applications. A literature study provided the bacteriophage PhiX174 as a potentially more suitable nonpathogenic coronavirus surrogate candidate. In irradiation experiments, the sensitivity of PhiX174 was investigated upon exposure to UV radiation of wavelengths 222 nm (Far-UVC), 254 nm (UVC), 302 nm (broad-band UVB), 311 nm (narrow-band UVB) and 366 nm (UVA) using a plaque assay. The determined log-reduction doses for PhiX174 were 1.3 mJ/cm2 @ 222 nm, 5 mJ/cm2 @ 254 nm, 17.9 mJ/cm2 @ 302 nm, 625 mJ/cm2 @ 311 nm and 42.5 J/cm2 @ 366 nm. The comparison of these results with published log-reduction doses of SARS-CoV-2 in the same spectral region, led to the conclusion that the bacteriophage PhiX174 exhibits larger log-reduction doses than SARS-CoV-2, nevertheless, it is a better UV-surrogate at 222 nm (Far-UVC), 254 nm (UVC) and 302 nm (UVB) than the often applied Phi6.